Basket making - Barratt, Olivia Elton (Tiger Books International Twickenham, U.K., 1998)
"Basket Making" is a comprehensive guide that explores the art and craft of creating baskets from various materials such as reeds, grasses, and synthetic fibers. The text delves into the history and cultural significance of basket weaving across different societies, highlighting traditional techniques and modern adaptations. It provides step-by-step instructions for beginners and experienced crafters alike, covering essential tools, methods, and design principles. Through vivid illustrations and practical tips, the book encourages creativity and sustainability in crafting, emphasizing the joy and satisfaction of making functional and beautiful baskets.